Military budgets of the G20 countries: structure and directions for improvement - S.V. Svirko; V.V. Dovhalyuk; V.O. Kuchmenko; T.M. Trosteniuk (Економіка, управління та адміністрування)
The current state of the security environment in the world has reached an extremely low level, which causes the need to review the approaches to the defense capability of each of the countries of the world as a whole, and the most powerful of them above all. The article examines the military budgets of the Big 20 countries and defines the key features of the structure of each of them. The elaboration of the 2014 Manual on State Finance Statistics, as well as the spread of the phenomenon of providing international military aid on an irreversible basis from foreign countries and international organizations to countries participating in military conflicts, motivated the need to expand the thesaurus of military finances and defense finances, which should include: incoming military capital transfers , incoming current military transfers, incoming capital military grants, incoming current military grants. Under incoming capital military transfers in the context of domestic realities, it is proposed to understand - transfers in kind and monetary forms, which involve: the transfer of ownership of a military asset (except for cash or circulating assets of military purpose) from international partners (governments of other countries or international organizations) to by our country represented by the Ministry of Defense of Ukraine, as the main manager of budget funds under the «Defense» function; the emergence of the obligation of our country in the person of the Ministry of Defense of Ukraine, as the main administrator of budget funds under the «Defense» function, to purchase a military asset (except for monetary funds or circulating assets of military purpose); voluntary termination of the obligation of the Ministry of Defense of Ukraine, as the main administrator of budget funds funds under the «Defense» function to purchase a military asset (except cash or current military assets) from international partners (governments of other countries or international organizations) with their refusal in the future to collect the debt. Incoming current military transfers, in turn, are transfers in kind and cash received from international partners (governments of other countries or international organizations) by our country in the person of the Ministry of Defense of Ukraine, as the main manager of budget funds under the function «Defence», which include all incoming military transfers except capital transfers. In turn, incoming capital military grants and incoming current military grants received the following appropriate interpretations: incoming capital military grants are incoming capital military transfers for a specific purpose; incoming current military grants are all other incoming targeted military transfers, except for capital. The proposed terms are distinguished by their correlation with the generally accepted terminology of international public finance, and also form logical subtypes of capital / current grants / transfers in the context of the implementation of the country’s defense function and its financial support. Their introduction into the state military finance subsystem will contribute to the development of a clear and effective mechanism for the formation, provision, use and control of military aid to the countries of the world.